Dietary Tomato or Lycopene Do Not Reduce Castration-Resistant Prostate Cancer Progression in a Murine Model. Issue 7 (5th May 2020) - Rowles, Joe L; Smith, Joshua W; Applegate, Catherine C; Miller, Rita J; Wallig, Matthew A; Kaur, Amandeep; Sarol, Jesus N; Musaad, Salma; Clinton, Steven K; O'Brien, William D; Erdman, John W
ABSTRACT: Background: Dietary tomato products or lycopene protect against prostate carcinogenesis, but their impact on the emergence of castration-resistant prostate cancer (CRPC) is unknown. Objective: We hypothesized that tomato or lycopene products would reduce the emergence of CRPC. Methods: Tr ansgenic a denocarcinoma of the m ouse p rostate (TRAMP) mice were castrated at 12–13 wk and the emergence of CRPC was monitored by ultrasound in each study. In Study 1, TRAMP mice ( n = 80) were weaned onto an AIN-93G-based control diet (Con-L, n = 28), a 10% tomato powder diet (TP-L, 10% lyophilized w/w, n = 26), or a control diet followed by a tomato powder diet after castration (TP-Int1, n = 26). In Study 2, TRAMP mice ( n = 85) were randomized onto a control diet with placebo beadlets (Con-Int, n = 29), a tomato diet with placebo beadlets (TP-Int2, n = 29), or a control diet with lycopene beadlets (Lyc-Int, n = 27) following castration (aged 12 wk). Tumor incidence and growth were monitored by ultrasound beginning at an age of 10 wk. Mice were euthanized 4 wk after tumor detection or aged 30 wk if no tumor was detected. Tissue weights were compared by ANOVA followed by Dunnett's test. Tumor volumes were compared using generalized linear mixed model regression. Results: Ultrasound estimates for the in vivo tumor volume were strongly correlated with tumor weight at necropsy (R 2 = 0.75 and 0.94, P <0.001 for both Studies 1 and 2, respectively). Dietary treatments after castration did not significantly impact cancer incidence, time to tumor detection, or final tumor weight. Conclusions: In contrast to studies of de novo carcinogenesis in multiple preclinical models, tomato components had no significant impact on the emergence of CRPC in the TRAMP model. It is possible that specific mutant subclones of prostate cancer may continue to show some antiproliferative response to tomato components, but further studies are needed to confirm this.